The relationship between self-efficacy and uncertainty avoidance levels of school administrators - Hamza Öz (Frontiers in Psychology)
Uncertainty and uncertainty avoidance are important factors affecting individuals’ decisions and behaviors. Uncertainty is defined as insufficient information to understand a situation or event or difficulty in coping with conflicting information. The concept of self-efficacy is defined as a person’s belief in their capacity to perform a certain task. This research, which was conducted to determine the relationship between the self-efficacy of school administrators and their levels of uncertainty avoidance, was designed according to the relational screening model in accordance with the quantitative research method. Another aim of the research is to determine whether the relationship between the self-efficacy of school administrators and their levels of uncertainty avoidance varies according to demographic variables. The universe and sample of the research consist of 243 school administrators who were selected from among school administrators working in a province in the Central Anatolian region of Turkey using the simple random sampling method. In the research, the “School Principals’ Self-Efficacy Perception Scale” was used to determine the self-efficacy perceptions of school administrators, and the “Uncertainty Avoidance Questionnaire” was used to determine their levels of uncertainty avoidance. The findings were interpreted in the context of the cultural values of the society in which the research was conducted. The most important results of the research are that the self-efficacy of school administrators is high, their levels of uncertainty avoidance are moderate, and the relationship between the self-efficacy of school administrators and their levels of uncertainty avoidance is low. Various suggestions were made in the context of the limitations of the study.